PEMANFAATAN LIMBAH PRODUKSI MIE SEBAGAI ALTERNATIF PAKAN TERNAK - Susi Agung Purwaningtyas; Sulhadi Sulhadi; Teguh Darsono; Aninditya Dwi Perwitasari (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2017)
Abstract One of the alternative utilization of wasted noodle production is to overcome the problem of limited amount of forage forage especially in the dry season. The purpose of this study to determine the nutrition of noodle wasted noodle production as an alternative to cattle feed. Before the nutrition testing, first the wasted noodle production enriched content. Noodle production waste is mixed with grass, rice bran, and straw. These materials are the usual feed ingredients given to cows and have been tested for their nutritional content. Rasum I obtained nutrient content: 28% crude fiber, 0.5% fine protein, 29% fat. Ration II of nutrition contained: crude fiber 24.6%, 0.5% fine protein, 25.6% fat. Ration III of nutrition contained: crude fiber 19.4%, protein 0.5%, fat 19.9 Keyword: Wasted noodles production, animal food